PERBANDINGAN PRODUKTIVITAS LUFFING CRANE DENGAN HAMMER HEAD CRANE PADA PROYEK HIGH RISE BUILDING STUDI KASUS: MENARA ASTRA PROJECT, JAKARTA - Putri Lokita Purnama Citra; Gloria Sihkawekas; Arif Hidayat; Rudi Yuniarto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2016)
The economic growth has contributed to the increasing number of high rise building construction mostly in big city especially Jakarta. In practice, the construction of high rise building project is aided by heavy equipment that is hammer head crane which is known as one of tower crane type. However, with the increasing number of high rise building construction, the hammer head crane space that usually be used in high rise building project is limited, hence, another type of tower crane called luffing crane that can be working optimally in the limited space is needed as the alternative for hammer head crane. For the consideration in choosing the type of which tower crane that should be used in the project, it requires the productivity analysis that is related to the equipment efficiency for each column, slab and beam works. From the research that has been conducted, it shows that the hammer head crane productivity is 13% higher fo column work and 65% higher for slab and beam works than luffing crane’s. With a note that in horizontal movement, luffing crane is excel more than hammer head crane. So overall, it can be concluded that in a condition where hammer head crane still can be operated in a limited space, its productivity is still higher than luffing crane productivity that operated in the same condition and surrounded. While luffing crane is used if hammer head crane is utterly can not be operated.